'He left me a message on Facebook': comparing the risk profiles of self-harming patients who leave paper suicide notes with those who leave messages on new media. Issue 3 (May 2016) - Barrett, Jessica R.; Lee, William; Shetty, Hitesh; Broadbent, Matthew; Cross, Sean; Hotopf, Matthew; Stewart, Robert
Abstract : Background: In cases of non-fatal self-harm, suicide notes are a major risk factor for repeated self-harm and suicide. Suicide notes can now be left on new media services, emails or text messages, as well as on paper. Aims: In a group of people who had harmed themselves, we aimed to compare new media note-leavers with paper note-leavers and characterise these groups demographically and by risk factors. Method: Clinical notes of patients who presented with non-fatal self-harm to two London emergency departments were anonymously searched for mentions of new media use. These were categorised and risk factors were compared for those who had left a new media note, a paper note, or no note to establish differences in risk of note-leaving. Results: New media note-leaving was associated with younger age and substance use; both risk factors for repeated self-harm. However, suicidal intent remained highest in paper note-leavers. Conclusions: Paper note-leavers remain at greatest risk, however new media note leaving is still correlated with risk factors related to repeated self-harm and suicide. Clinicians should enquire about new media use during emergency department assessments of self-harm.